How much is road infrastructure worth? - Rodríguez, Marcos (2025)
In general, drivers and pedestrians use roads, bridges, sidewalks, intersections, traffic lights, informational signs, and other elements without realizing how much their construction and maintenance have cost the country. It is only occasionally, such as when a user reaches a toll booth on a highway, that they are directly confronted with the reality that road infrastructure has a cost that society as a whole must finance or pay in order to benefit from its service.